Extended Bioethics as a Response to Global Biological Consciousness - Isea, Raul (Journal of Current Scientific Research, 2025)
Humanity is persistently threatened by global pandemics- exemplified by the Black plague, the Spanish flu, and COVID-19, which reveal a continual absence of concern in real-time prevention. To forecast biological threats in the future and spur proactive human response, the term Global Biological Consciousness (GBC) is introduced.GBC requires an Extended Bioethics, a dynamic ethical framework for conscious management mediated by GBC. This perspective will enable preventive actions and will seek global biological resilience through the algorithmic responsibility of AI and systemic justice, as will be explained in the work. The GBC, through Extended Bioethics, will provide an ability to analyze biological data as it occurs using AI and quantum computing, expect outbreaks before they happen and attenuate their effects, here creates a new ethical contract for all humankind as they co-exist in a biological world.
Keywords: Bioethics; Resilience; Global Biological Consciousness; Artificial Intelligence